Silver–Graphene Oxide Nanohybrids for Highly Sensitive, Stable SERS Platforms - Kasztelan, Mateusz; Studzinska, Anna; Żukowska, Grażyna Zofia; Pałys, Barbara (Frontiers in Chemistry, 2021)
Graphene oxide– silver nanoparticle nanohybrids were synthesized by simple reduction of the silver nitrate and graphene oxide (GO) mixture in water by the mild reducing agent - ascorbic acid. The concentration of ascorbic acid was varied to verify the possible influence of the GO surface composition on the efficiency of the hybrid material as substrates for surface enhanced Raman spectroscopy (SERS). Further, the composites were conditioned in ammonia solution or in potassium hydroxide diluted solution. For comparison the graphene oxide – silver nanoparticles composite has been synthesized using the ammonia treated GO. All materials were characterized by spectroscopic and microscopic methods including UV-Vis, infrared and Raman spectroscopy and scanning electron microscopy. The SERS efficiency of the nanohybrids was tested using 4-aminothiophenol (PATP). The optimal synthesis conditions were found. Ammonia and potassium peroxide drop-casted on the composite change the SERS properties. The sample treated with KOH shows best SERS enhancement. The variation of the SERS enhancement is correlated with the shape of the UV-Vis characteristics and the surface structure of the composites.